Lingual focal hyperplastic lesion in a pediatric patient : report of an unusual case = Lesión hiperplásica focal lingual en un paciente pediátrico : informe de un caso inusual - Herrera B, Denisse A.
Focal fibrous hyperplasia (FFH) is an oral mucosal localized non-neoplastic enlargement representing a reaction to chronic local irritations or injuries. The purpose of this report is to describe the management of an asymptomatic fibrotic lesion located in the tongue, in a preschooler boy. A 7-year-6-month old boy attended our clinic for the evaluation of an exophytic pedunculated tumor-like round mass located in the dorsal surface of the tongue. Based on the initial examination and the natural history of the lesion, the presumptive clinical diagnosis determined an irritation FFH. The lesion was surgically excised with a diode laser device, and the postoperative period evolution occurred without any complication. The appropriate treatment of FFH in children initially consists of the removal of local irritant factors. Excellent oral hygiene maintenance and close follow-up care are strongly suggested. Surgical excision is the most frequent modality for persistent lesions. Early diagnosis and proper management of FFH can reduce the risk of future recurrences or complications.